2018
DOI: 10.1016/j.bja.2018.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Implicit aversive memory under anaesthesia in animal models: a narrative review

Abstract: Explicit memory after anaesthesia has gained considerable attention because of its negative implications, while implicit memory, which is more elusive and lacks patients' explicit recall, has received less attention and dedicated research. This is despite the likely impact of implicit memory on postoperative long-term well-being and behaviour. Given the scarcity of human data, fear conditioning in animals offers a reliable model of implicit learning, and importantly, one where we already have a good understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 137 publications
0
12
0
Order By: Relevance
“…Samuel et al previously demonstrated there is a response difference between front and hind paw withdrawal, with the hind paw withdrawal being a more valuable indicator of a surgical anesthesia plane in mice. 13 During the initial anesthesia induction (depending on the type of anesthetic used, route of administration of anesthesia, mouse age and strain), the anesthesia plane will continuously evolve into a deeper plane. For example, when using injectable ket/xyl anesthesia in mice, it can require between 6 and 20 minutes to reach a surgical anesthesia plane depending on the mouse strain and route of administration.…”
Section: Anesthetic Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Samuel et al previously demonstrated there is a response difference between front and hind paw withdrawal, with the hind paw withdrawal being a more valuable indicator of a surgical anesthesia plane in mice. 13 During the initial anesthesia induction (depending on the type of anesthetic used, route of administration of anesthesia, mouse age and strain), the anesthesia plane will continuously evolve into a deeper plane. For example, when using injectable ket/xyl anesthesia in mice, it can require between 6 and 20 minutes to reach a surgical anesthesia plane depending on the mouse strain and route of administration.…”
Section: Anesthetic Monitoringmentioning
confidence: 99%
“…In addition to an anesthetic’s ability to alter consciousness, anesthetics impact memory (ie, cause amnesia). 4 , 5 , 9–11 Though we have a limited ability to assess amnesia in animals, previous studies have shown amnesia secondary to anesthesia in a variety of animal species, including mice, 12 , 13 rats, 13 , 14 and zebrafish. 15 Thus, properly induced and conducted general anesthesia is expected to produce amnesia in laboratory animals.…”
Section: Introductionmentioning
confidence: 99%
“…The age-induced decline of implicit memory (e.g., priming) is less than the decline of explicit memory (e.g., recognition) [ 79 ]. Explicit memory and implicit memory involve different parts of the brain: while the hippocampus is necessary for explicit memory, the amygdala, a small structure located near the hippocampus, is essential for implicit memory formation [ 80 ]. A surgery-induced stress response causing elevated norepinephrine levels and amygdala activity (in addition to other regions) would facilitate the implicit learning of emotionally negative information presented during anesthesia [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, most of the deep sedation regimens were based on propofol or midazolam, two γ-aminobutyric acid type A receptor agonists with an amnestic effect [ 80 ], which were administered in the absence of opioids and NMBAs, at a dosage to prevent a reaction following repeated or painful stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, conditioned taste aversion should be explicit by their definition-but this does not seem to be the case. For example, conditioned taste aversion in rats is still acquired when the illness-inducing outcome is delivered under general anesthesia (Bermudez-Rattoni et al, 1988;Samuel et al, 2018). Also, in humans undergoing cancer treatment, conditioned taste aversions are formed despite the patients being aware that their illness/nausea is produced by the treatment and not the novel foods eaten (Bernstein & Webster, 1980).…”
Section: Classical Conditioningmentioning
confidence: 99%